A liquid crystalline precursor incorporating chlorhexidine acetate and silver nanoparticles for root canal disinfection. (6th February 2018) - Zheng, Tengyi; Huang, Xintian; Chen, Jintian; Feng, Disang; Mei, Liling; Huang, Ying; Quan, Guilan; Zhu, Chune; Singh, Vikramjeet; Ran, Hao; Pan, Xin; Wu, Chuan-Yu; et al.
Abstract : The transformation of cubic lyotropic liquid crystals in root canals on coming into contact with water provided long-lasting disinfection against multidrug-resistant bacteria to avoid the endodontic reinfection and follow-up visit. Abstract : Lyotropic liquid crystals (LLC) have received increasing attention as a drug delivery system. In this study, a novel intra-canal disinfectant based on the glycerol monooleate (GMO) LLC precursor incorporation with chlorhexidine (CHX) and silver nanoparticles (Ag-NPs) was designed and evaluated. The LLC precursor with excellent fluidity was able to penetrate deeply into the complex tiny collateral branch root canals. The transformation of cubic LLC in root canals upon coming into contact with water provided long-lasting disinfection against multidrug-resistant bacteria to avoid the endodontic reinfection and follow-up visits. The GMO–ethanol–water (48% : 12% : 40%, w/w) formulation containing 0.5% CHX and 0.02% Ag-NPs was selected for further studies. The low viscosity of the precursor presented excellent injectability and flowabilities. From the in vitro release test, the release behaviours were found to be influenced by CHX and Ag-NP contents, allowing the optimized precursor to obtain a 28-day release profile. The CHX-Ag-NP containing LLC precursor exhibited an excellent and sustained sterilization effect on Enterococcus faecalis for more than one month with a bacterial inactivation rate of ≥98.5%, which was far more than the minimum clinical requirement (7 days). Furthermore, no in vitro toxicity was observed in the cytotoxicity evaluation. The CHX-Ag-NP containing LLC precursor was proved to be a promising intra-canal disinfectant in our study.